Coeval early Ediacaran breakup of Amazonia, Baltica, and Laurentia: evidence from Micro‐Baddeleyite dating of dykes from the Novillo Canyon, Mexico - Weber, Bodo; Schmitt, Axel Karl; Cisneros de León, Alejandro (Geophysical research letters, 2019)
Final Rodinia supercontinent breakup during the early Ediacaran is recorded by mafic dyke swarms in Baltica and Laurentia, but corresponding dykes have been elusive for Amazonia, the third craton involved. We report ages and compositions for plume‐related dykes intruded into Rodinia‐type basement of the Novillo Gneiss, part of a microcontinent placed between Amazonia and Baltica in Rodinia reconstructions. In situ U‐Pb micro‐baddeleyite dating with secondary ion mass spectrometry yielded dyke intrusion ages of 619 ± 9 Ma (95% c.i.), coeval with ages of similar dykes from Baltica and Laurentia. A younger age group is consistent with an earlier 40Ar‐39Ar age at ~545 Ma, reflecting Pb loss and recrystallization during hydrothermal alteration. The results indicate an Amazonia‐Baltica‐Laurentia connection prior to opening of the Iapetus Ocean and suggest a previously unrecognized superplume‐related large igneous province extending over all sides of the former triple point. Weathering of these large igneous province basalts may have contributed to Ediacaran Gaskiers glaciation.